2022
DOI: 10.1002/pmrj.12869
|View full text |Cite
|
Sign up to set email alerts
|

Race, ethnicity, and utilization of outpatient rehabilitation for treatment of post COVID‐19 condition

Abstract: Introduction Outpatient rehabilitation is recommended in the treatment of post coronavirus disease 2019 (COVID‐19) condition. Although racial and ethnic disparities in the incidence and severity of COVID‐19 have been well documented, little is known about the use of outpatient rehabilitation among patients with post COVID‐19 condition. Objective To examine factors associated with outpatient rehabilitation use following COVID‐19 and to ascertain whether differential incidence of sequelae explain variation in po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Awareness was raised early on with physical medicine and rehabilitation recommendations, in an effort to minimize disability, improve QoL and ensure the quickest return to everyday life ( 18 , 19 ). However, a recent large-scale nationwide study from the United States concluded that use of rehabilitation services was associated with race, although the incidence of post-COVID symptoms was no different, with black and Latino patients being underrepresented in the group of people seeking post-COVID help ( 20 ). A Latino American study revealed a heterogeneous pattern of rehabilitation provision within the region, with most of the programmes focusing on physiotherapy ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Awareness was raised early on with physical medicine and rehabilitation recommendations, in an effort to minimize disability, improve QoL and ensure the quickest return to everyday life ( 18 , 19 ). However, a recent large-scale nationwide study from the United States concluded that use of rehabilitation services was associated with race, although the incidence of post-COVID symptoms was no different, with black and Latino patients being underrepresented in the group of people seeking post-COVID help ( 20 ). A Latino American study revealed a heterogeneous pattern of rehabilitation provision within the region, with most of the programmes focusing on physiotherapy ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…During the COVID-19 pandemic, investigators from Greece reported 145 patients hospitalized for COVID-19, of whom 46.7% had severe disease and at 4 mo 4.3% had been referred to rehabilitation services 5. Hentschel and colleagues6 examined use of outpatient rehabilitative services in 8724 individuals diagnosed with COVID-19 and reported that 0.86% of previously hospitalized patients participated in rehabilitative services. Although PR services were limited during the pandemic, single-center reports described improvements in PR participants with post-COVID syndrome 7,8.…”
Section: Discussionmentioning
confidence: 99%
“…Although referral for ongoing outpatient physical and occupational therapy is beneficial, there remain significant gaps in health equity for certain populations. In a recent large national case–control study, African‐American/Black individuals were significantly less likely to receive outpatient rehabilitation than their white counterparts (odds ratio = 0.89) 88 . Specific to pain management, African‐American persons continue to experience disparities in the prevalence, management, progression, and outcomes of chronic, nonmalignant pain‐related conditions 89 …”
Section: Common Neurologic Sequelae and How To Best Guide Carementioning
confidence: 99%